TO THE QUESTION OF RELEVANCE OF FORMATION VERBAL COMPETENCES OF STUDENTS TECHNICAL UNIVERSITY - Elena N. Ryabinova; Larisa A. Marchenkova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Relevance of formation of verbal competences of graduates of technical university in the course of their vocational training is considered. Need of development it is professional - speech communication in the course of training of future engineers it is connected with that a number of essential differences from liberal arts college has technical education. It is connected with prevalence of the disciplines based on the exact sciences, and the organization of educational activity more accurately structured. For technical college specific style of relationship of students and teachers - less subjective and emotional, more rational, rigid and rectilinear is characteristic. For manifestation of creative activity in engineering activity the general indicators of intellectual achievements, sotsial-but-mental sets and personal characteristics matter (emotional and strong-willed and communicative). Results of pilot studies allowed to draw a conclusion that an intellectual factor - development of verbal and nonverbal intelligence, high-speed characteristics of thinking - has backbone value for creative activity in engineering activity. The traditional content of the humanitarian disciplines taught at technical universities is de-prived of a professional orientation and doesn't consider feature of engineering activity. It creates need of formation of verbal competences of students of technical university in the course of their vocational training which has to be combined harmoniously with main objec-tives, consider prospects of development of the higher technical education at a stage of for-mation of the new educational concept. It is shown that future engineer demands formation of verbal kompetentnost of students in technical university: ability to perceive, analyze, generalize information; to gain new knowledge, to operate own rechemyslitelny process; to masterfully use written and oral speech in various genres of a scientific and official style; with deep arguments to state own point of view, messages of polemic and discussion.